Field Evaluation of Recombinant Antigen ELISA in Detecting Zoonotic Schistosome Infection Among Water Buffaloes in Endemic Municipalities in the Philippines - Angeles, Jose Ma. M.; Goto, Yasuyuki; Kirinoki, Masashi; Villacorte, Elena A.; Moendeg, Kharleezelle J.; Rivera, Pilarita T.; Chigusa, Yuichi; Kawazu, Shin-ichiro (Frontiers in Veterinary Science, 2020)
In this study, we investigated the use of recombinant antigens thioredoxin peroxidase-1 (rSjTPx-1) and tandem repeat rSj1TR in evaluating the antibody positivity rates of Schistosoma japonicum infection among water buffaloes from four endemic areas in the Philippines, two municipalities with high endemicity (Calatrava, Negros Occidental and Catarman, Northern Samar) and two municipalities nearing elimination with no cases of human schistosomiasis (Talibon and Trinidad, Bohol). These recombinant antigen ELISA assays were compared with other diagnostic tests including SEA-ELISA, FECT and fecal-based PCR. Results showed that rSj1TR-ELISA has the highest agreement with PCR in all study areas. Furthermore, significant positivity rates among water buffaloes were seen in Talibon and Trinidad, indicating that water buffaloes are maintaining the schistosome parasites in transmission areas even in the absence of human infection. Hence, serological assay using a more sensitive and specific rSj1TR-ELISA can be used for animal surveillance to prevent emergence and re-emergence of human schistosomiasis.